Temporal expression of late histone messenger RNA in the sea urchin Lytechinus pictus. - Knowles, J A (1984)
Sea urchin histones are encoded by several multigene families. The temporal expression of one of these families, the late histones, has been studied during the early development of Lytechinus pictus. Using a nuclease S1 assay, we detected about 10,000 transcripts encoding both late H3 and H4 proteins in the unfertilized egg. This suggests that the late genes were active at some point during oogenesis. The number of late gene transcripts begins to increase 6.5 hr after fertilization (64-cell stage), indicating that these genes probably become reactivated 4.5-6.5 hr after fertilization. The maximum rate of accumulation of transcripts (4600 molecules per min per embryo) occurs 9-14 hr after fertilization (from blastula stage to hatching). The number of transcripts peaks 21 hr after fertilization (onset of gastrulation) when the embryo has accumulated 1.8 X 10(6) copies of each late mRNA (a 164-fold increase). A 5.5-fold increase in the relative rate of transcription, between 7 and 15 hr after fertilization, is partly responsible for the accumulation of these gene products. The relative synthesis of early histone message, which is encoded by a different family, decreases 18-fold during this time. Synthesis of the late transcripts continues at the higher rate after accumulation has ceased (24 hr after fertilization). The number of late transcripts begins to decrease 48 hr after fertilization, reaching about 10,000 copies at 72 hr.